Evaluation of a flexible and integrative psychiatric care model in a department of child and adolescent psychiatry in Tübingen, Germany: study protocol (EVA_TIBAS) - Neumann, Anne; Hense, Helene; Baum, Fabian; Kliemt, Roman; Seifert, Martin; Harst, Lorenz; Kubat, Denise; Maicher, Birgit; Schrey, Christopher; Schmitt, Jochen; Pfennig, Andrea; Weinhold, Ines; et al. (BMC health services research, 2021)
Background Model projects for flexible and integrated treatment (FIT) in Germany aim at advancing the quality of care for people with mental disorders. A new FIT model project was established in 2017 at the Department of child and adolescent psychiatry (KJP) of the University Hospital Tübingen (Universitätsklinikum Tübingen, UKT). The study design of EVA_TIBAS presented here describes the evaluation of the FIT model project at the KJP of the UKT. This evaluation aims at quantifying the anticipated FIT model project changes, which are to improve patients’ cross-sectoral care at the same maximum cost as standard care. Methods EVA_TIBAS is a controlled cohort study using a mix of quantitative and qualitative methods. The FIT evaluation consists of three modules. In Module A, anonymized claims data of a statutory health insurance fund will be used to compare outcomes (duration of inpatient and day care psychiatric treatment, inpatient and day care psychiatric length of stay, outpatient psychiatric treatment in hospital, inpatient hospital readmission, emergency admission rate, direct medical costs) of patients treated in the model hospital with patients treated in structurally comparable control hospitals (estimated sample size = ca. 600 patients). In Module B, patient-reported outcomes (health related quality of life, symptom burden, return to psychosocial relationships (e.g. school, friends, hobbies), treatment satisfaction, societal costs) will be assessed quantitatively using validated questionnaires for the model and two control hospitals (estimated sample size = ca. 300 patients). A subsequent health economic evaluation will be based on cost-effectiveness analyses from both the insurance fund’s and the societal perspective. In Module C, about 30 semi-structured interviews will examine the quality of offer, effects and benefits of the service offered by the social service of the AOK Baden-Württemberg (for stabilizing the overall situation of care in the family) in the model hospital. A focus group discussion will address the quality of cooperation between employees of the university hospital and the social services. Discussion The results of this evaluation will be used to inform policy makers whether this FIT model project or aspects of it should be implemented into standard care. Trial registration This study was registered at ClinicalTrials.gov PRS (ID: NCT04727359 , date: 27 January 2021).